Stereospecific polymerization of isoprene - Ceausescu, Elena (Pergamon, 1983)
Stereospecific Polymerization of Isoprene, a doctoral dissertation by Dr. Elena Ceausescu, is a study of the synthesis of cis-l, 4-polyisoprene rubber, an elastomer of synthetic rubber whose structure and properties are similar to that of natural rubber. This elastomer is primarily used in the manufacture of tires, belts, hoses, matting, flooring, dampeners, and other synthetic rubber goods. The book is organized into two parts. Part I, the Ph. D. thesis, focuses on the explanation and exposition of the polymerization reaction; properties of the polymer; and certain theoretical aspects related.